Researching visible policing - Ralph, Liam (Introduction to policing research, 2024)
In 2019, the authors of this chapter embarked on a two-year ESRC funded research project entitled ‘Visible Policing’. Research was conducted with police officers, police staff, architects and citizens, and both offline and online in connection to three distinct aspects of police visibility. This included the police estate, police artefacts reflecting police material culture, and police use of social media. The chapter draws on this project to argue for greater use of visual methods in policing. Further, the chapter illustrates how policing scholars can use researcher-generated and participant-generated visual data. As is shown, visual methods have rarely been applied in policing research despite the significance of police visibility that has endured over time.